Original articleExpression of genes FOLR1, BAG1 and LAPTM4B in functioning and non-functioning pituitary adenomas - Larysz, Dawid; Żebracka-Gala, Jagoda; Rudnik, Adam; Hasse-Lazar, Kornelia; Kowalska, Małgorzata; Jarząb, Michał; Król, Aleksandra; Szpak-Ulczok, Sylwia; Bażowski, Piotr; Jarząb, Barbara (Folia Neuropathologica, 2012)
Introduction : The mechanism of pathogenesis of adenomas pituitary is still unknown; differences between pituitary cells of different origin are observed. Identification of genes specific to pituitary adenomas should give better understanding of differences in their response to therapy, especially to radiotherapy. The aim of our study was to independently validate differences in the expression of FOLR1, BAG1, LAPTM4B between functioning (FA) and non-functioning (NFA) pituitary adenomas reported by microarray-based studies. Material and methods: Analysis of gene expression was performed by real-time quantitative PCR (QPCR) in 76 pituitary adenomas, 25 functioning and 51 non-functioning ones. The expression of the examined genes was normalized to the reference index, obtained by calculation of the geometric mean of reference genes expression: GUS-B, B2M, ACTB, EIF3S10, UBE2D2 and ATP6V1E. Results : Two genes showed significant differences in expression between non-functioning adenomas and functioning ones (FA) (FOLR1 32.4 x greater p = 0.022, BAG1 2.2 x lower p = 0.0002). The expression of LAPTM4B (1.1 x lower) was only insignificantly changed. The expression of FOLR1 in all tumours (functioning and non-functioning) was higher in older patients (over 50 years of age) (p = 0.018). Expression of BAG1 was significantly lower in older patients (p = 0.015). In a subgroup of pure non-functioning adenomas there was a higher expression of FOLR1 in older patients (p = 0.006). Analysis of expression profiles and invasiveness of tumours did not reveal any significant differences both in non-functioning and functioning tumours. Conclusions: Among pituitary adenomas, the highest level of expression FOLR1 is seen in NFA which are negative by immunohistochemistry to all pituitary hormones while GH-producing adenomas are the only class of pituitary tumours where FOLR1 expression is virtually absent. For BAG1 we confirm a significantly higher expression in functioning (both PRL and GH producing) adenomas than non-functioning ones, while LAPTM4B does not exhibit any expression changes between different classes of pituitary tumours.